Conceptualizing East Asian ‘Enemy-Shore Islands’ : The Cases of the Five West Sea Islands of South Korea and the Kinmen and Matsu Islands of Taiwan - Ristimäki, Aino (My University, 2026)
This thesis conceptualizes the Five West Sea Islands (FWI) of South Korea, and Kinmen and Matsu Islands (Kinma) of Taiwan as enemy-shore islands. Enemy-shore islands are border islands that are located offshore of their authoritative country, but onshore of an enemy-country. On one hand, these islands are utilized by the central government to help govern the enemy-border as well as national security. On the other hand, though, enemy-shore islands are an entity that essentially shapes these governance practices and the enemy-relation between the two countries. This kind of duality is the central claim of this thesis. Such a duality causes an inherent policy dilemma for policymakers. At the same time, enemy-shore island policies like militarization, development, restrictions and cross-border cooperation must have aspects to them that enhance the utilization of enemy-shore islands in maintaining governance practices, while the same policies also should protect the islands and compensate their residents. Moreover, this thesis proposes that the imposing of these policies partially shape the realities and trajectories of the enemy-shore islands and their residents.
Keywords: South Korea; Taiwan; conceptualization; border regions; enemy-shore island